2013
DOI: 10.1097/aln.0b013e318289bafe
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Survival from Perioperative Cardiopulmonary Arrests

Abstract: Background Perioperative cardio-pulmonary arrests are uncommon and little is known about rates and predictors of in-hospital survival. Methods Using the Get-With-The-Guidelines – Resuscitation national cardiopulmonary resuscitation registry, we identified all patients aged 18 years or older who experienced an index, pulseless cardiac arrest in the operating room or within 24 hours postoperatively. The primary outcome was survival to hospital discharge, and the secondary outcome was neurologically intact reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
2
9

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(38 citation statements)
references
References 20 publications
2
25
2
9
Order By: Relevance
“…Finally, we demonstrated that survival after intraoperative CPR is six times higher than survival after postoperative CPR. This observation has been shown in other studies, [17] and could be related to the fact that intraoperative cardiac arrest is witnessed, with known likely culprit and availability of resources for immediate treatment.…”
Section: Discussionsupporting
confidence: 68%
“…Finally, we demonstrated that survival after intraoperative CPR is six times higher than survival after postoperative CPR. This observation has been shown in other studies, [17] and could be related to the fact that intraoperative cardiac arrest is witnessed, with known likely culprit and availability of resources for immediate treatment.…”
Section: Discussionsupporting
confidence: 68%
“…This rate exceeds those previously reported after in-hospital cardiac arrest in an obstetric population in Belgium (17%), 19 in-hospital cardiac arrest in a nonobstetric population in the United States (21.2%), 20 perioperative cardiac arrest for nonobstetric surgery in the United States (31.7%), 21 and in a population of pregnant arrest victims described in a systematic review of published case reports (54%). 22 This high survival rate may reflect the relative health and fitness of the childbearing population, or the inclusion of postpartum cardiac arrest events.…”
Section: Discussioncontrasting
confidence: 51%
“…Entre estes, citam-se: o maior grau de disfunção orgânica à admissão na UTI, fibrilação ventricular como o primeiro ritmo de PCR, o uso de adrenalina após a PCR, pior status neurológico pré-PCR, maior idade, maior duração da RCP e até o local do hospital onde o evento ocorreu (5,6). Entretanto, estes estudos analisam desfechos temporais distintos, sendo que alguns focam a alta hospitalar, enquanto outros focam tempos específicos, com limite superior de 90 dias (5, 6).…”
Section: Parada Cardiorrespiratória (Pcr) é Definida Pela "American Hunclassified
“…Além disso, a PCR intraoperatória tem sido associada a elevada letalidade, com taxas que atingem mais de 65% de óbito antes da alta hospitalar (5 Este autor dividiu os pacientes em grupos com valores de escala acima de 10 ou abaixo de cinco, permitindo, assim, uma sensibilidade de 96% e especificidade de 86%, com valores preditivos positivos e negativos de 77% e 97%, respectivamente (61).…”
Section: Consequências E Fatores Associados à Pcrunclassified
See 1 more Smart Citation